Elverne Salomon correspondence - Salomon, Elverne
Letter from Salomon addressed to President Franklin D. Roosevelt describing the Revolutionary War activities of Cornelius C. Vermeule in Somerset County, N.J., and proposing that a monument be erected to him.
Resident of Irvington, N.J.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Vermeule, Cornelius C., -- -1784.; New Jersey -- History -- Revolution, 1775-1783.; Somerset County (N.J.) -- History; United States -- History -- Revolution, 1775-1783 -- Monuments